2005
DOI: 10.1007/s00167-005-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of toe flexor tendoscopy in management of an unusual cause of metatarsalgia

Abstract: The purpose of this study is to describe an endoscopic approach to toe flexor tendons at the level of metatarsal head region. And this study is a kind of retrospective case series. Three patients with toe flexor tenosynovitis were evaluated after a follow-up of 2 years after toe flexor tendoscopy. One patient suffered from infective toe flexor tendosynovitis resulting from a penetrating injury and other two patients suffered from idiopathic focal toe flexor tenosynovitis. Pre-operative metatarsalgia subsided a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The presence of chronic peroneal tendon subluxation or dislocation and peroneal tenosynovitis presents with chronic peroneal pain and swelling [14]. Peroneal tendon injuries or degeneration especially if Clinical studies related to tendoscopic management of other tendon sheaths have been already published for stage 1 tibialis posterior tendon dysfunction [2,18] and for toe flexors [11]. Authors of both studies concluded that tendoscopic management is an effective and minimal invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of chronic peroneal tendon subluxation or dislocation and peroneal tenosynovitis presents with chronic peroneal pain and swelling [14]. Peroneal tendon injuries or degeneration especially if Clinical studies related to tendoscopic management of other tendon sheaths have been already published for stage 1 tibialis posterior tendon dysfunction [2,18] and for toe flexors [11]. Authors of both studies concluded that tendoscopic management is an effective and minimal invasive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The zone 3 FHL tendon is examined with the toe flexor tendoscopy [3]. A plantar toe portal is created with a transverse skin incision close to the insertion of the FHL tendon.…”
Section: Description Of Techniquementioning
confidence: 99%
“…Open exploration of the tendon usually requires extensive soft tissue dissection. Different tendoscopies of the foot and ankle have been described before [2][3][4][5]. We describe a tendoscopic approach to deal with the flexor hallucis tendon pathology.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive soft tissue dissection may result in painful scarring especially on the plantar side. Recently, techniques such as FHL tendoscopy 5,6 and arthroscopy of the metatarsosesamoid compartment [7][8][9] have been reported. For performing tendoscopy, the FHL tendon can be divided into 3 zones: zone 1 from the musculotendinous junction to the fibro-osseous orifice of the posterior talar processes; zone 2 from the orifice to the master knot of Henry; and zone 3 from the master knot of Henry to phalangeal insertion of the tendon.…”
mentioning
confidence: 99%
“…Zone 3 FHL tendoscopy provides access to the FHL tendon around the MTP-1 joint. 5,6 These techniques together with the classic MTP-1 arthroscopy allow thorough exploration and debridement of the MTP-1 joint and the flexor tendon sheath. The purpose of this Technical Note is to report the combined arthroscopic and tendoscopic approaches to address the MTP-1 joint and FHL tendon pathologies.…”
mentioning
confidence: 99%